On the identity of Ischaemum elimalayanum (Poaceae: Andropogoneae: Ischaemineae) with brief taxonomic notes on some allied congeners from India - Landge, Shahid Nawaz; Shinde, Rajendra D. (Phytotaxa, 2024)
In our examination of Ischaemum specimens from the BSI herbarium, originating from Karnataka, previously misidentified as Ischaemum semisagittatum, I. dalzellii, I. lanatum, and I. molle, we affirm that these specimens correspond to I. elimalayanum. This species, previously thought to be endemic to Kerala, aligns with the protologue and type specimens examined at CAL, K & MH herbaria. Accurate identification is facilitated by provided images based on specimens housed at BSI. Morphological investigations led to the inclusion of I. kumarakodiensis and I. abrahamii, closely related Kerala species, as new heterotypic synonyms of I. elimalayanum, substantiated by detailed comparative morphological analysis (Table 1) and taxonomic discussion. A key to aid identification of closely allied species in India is presented. The distribution map of I. elimalayanum is updated based on literature and herbarium specimens. Our study rectifies previous misidentifications, contributing to the taxonomy and distribution understanding of Ischaemum species in India. In addition, brief taxonomic notes on I. barbatum, I. pappinisseriensis and I. amboliense are given.